Respuesta :
Answer:
D
Step-by-step explanation:
Given the 2 equations
2x + 3y = 11 → I(1)
y = x - 3 → (2)
Substitute y = x - 3 into (1)
2x + 3(x - 3) = 11 ← distribute parenthesis and simplify left side
2x + 3x - 9 = 11
5x - 9 = 11 ( add 9 to both sides )
5x = 20 ( divide both sides by 5 )
x = 4
Substitute x = 4 into (2) for corresponding value of y
y = 4 - 3 = 1
Solution is (4, 1 ) → D
The correct ordered pairs for the equations 2x+3y=11, y=x-3 is (4,1)
What is a substitution method?
In the substitution method we have to calculate the value of one variable by putting the value of another variable in terms of first variable.
How to use substitution method?
We are having two equations
2x+3y=11.......1
y=x-3........2
Put the value of y from2 in 1
2x+3(x-3)=11
2x+3x-9=11
5x=20
x=4
put the value of x=4 in 2
y=4-3
y=1
Hence the ordered pairs becomes (4,1)
Learn more about substitution method at https://brainly.com/question/22340165
#SPJ2